SOCIAL EDUCATION: BUILDING CHARACTER AND CARE IN SOCIETY - Wisnu Wardoyo; Moh. Imron Rosidi; Melyana R Pugu (Adisam Publisher, 2025)
Social education is an integral part of the educational process that focuses on developing students' character and social awareness. Social education is key in shaping individuals who not only excel academically, but are also aware and concerned about social issues and have a strong character. The study conducted in this research uses the literature research method. The results show that; firstly, the integration of social values early on in the curriculum and school activities has a positive impact on students' behaviour and attitudes, enriches learning experiences, and instils a sense of social responsibility. Secondly, there are challenges such as difficulties in integrating the social education curriculum, the need for more intensive teacher training and barriers related to socio-economic and cultural diversity in the classroom. Thirdly, the effectiveness of social education largely depends on the quality and preparedness of teachers in designing and implementing a curriculum that includes a social component, as well as their ability to respond to the needs of diverse students. Social education requires students' active participation in projects and activities that promote empathy and social care. Inclusively and contextually designed curricula and adaptive teaching methods are proven to increase students' interest and participation in social learning.